2021
DOI: 10.52547/qums.15.1.66
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acceptance and Commitment Therapy on Depression and Anxiety in Patients With Hypertension

Abstract: Background and Objectives: Failure to treat hypertension often leads to fatal complications; thus, there is an urgent need to develop and expand effective psychological interventions in this respect. Therefore, this study aimed to determine the effects of Acceptance and Commitment Therapy (ACT) on depression and anxiety in patients with hypertension. Methods This was a quasi-experimental study with a pre-test, post-test and a control group design. In total, 24 patients with hypertension in Birjand city, Iran, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…[51] Additionally, a quasi-experimental pretest-posttest study reported that REBT was effective in lowering depression in patients with hypertension during the posttest and follow-up period. [52] In another previous study among 23 education undergraduates with the major depressive disorder at a Nigerian university, the authors found that REBT was successful in lowering depression ratings among the students. [53] More so, some researchers conducted a study to determine the cost-effectiveness and cost-utility of REBT in treating depression among a Romanian sample of 170 depressed clients.…”
Section: Discussionmentioning
confidence: 99%
“…[51] Additionally, a quasi-experimental pretest-posttest study reported that REBT was effective in lowering depression in patients with hypertension during the posttest and follow-up period. [52] In another previous study among 23 education undergraduates with the major depressive disorder at a Nigerian university, the authors found that REBT was successful in lowering depression ratings among the students. [53] More so, some researchers conducted a study to determine the cost-effectiveness and cost-utility of REBT in treating depression among a Romanian sample of 170 depressed clients.…”
Section: Discussionmentioning
confidence: 99%
“…(McCracken et al, 2013) meneliti penerapan terapi menggunakan konsep penerimaan, komitmen, dan tindakan dengan model singkat menunjukkan kelompok yang diberikan intervensi menunjukkan adanyan penurunan kecacatan, penurunan depresi dan kecemasan serta adanya penerimaan kondisi kesehatan. Pengaruh lain ACT yaitu membantu dalam manajemen diri pasien hipertensi, memperbaiki masalah psikologis, mengurangi sensitifitas kecemasan dan meningkatkan kualitas hidup pasien (Miri et al, 2021;Saibi et al, 2020;Yagi et al, 2022). ACT membantu dalam mengatur emosi kognitif dan mengidentifikasi ancaman yang dirasakan saat ini, sehingga dapat langsung mengatasi permasalannya (Zargar et al, 2019).…”
Section: Pembahasanunclassified